Klezmer America : Jewishness, ethnicity, modernity - Freedman, Jonathan, 1954- (Columbia University Press, 2008)
Klezmer is a continually evolving musical tradition that grows out of Eastern European Jewish culture, and its changes reflect Jews' interaction with other groups as well as their shifting relations to their own history. But what happens when, in the klezmer spirit, the performances that go into the making of Jewishness come into contact with those that build different forms of cultural identity? Jonathan Freedman argues that terms central to the Jewish experience in America, notions like "the immigrant," the "ethnic," and even the "model minority," have worked and continue to intertwine the Jewish-American with the experiences, histories, and imaginative productions of Latinos, Asians, African Americans, and gays and lesbians, among others. He traces these relationships in a number of arenas: the crossover between jazz and klezmer and its consequences in Philip Roth's The Human Stain; the relationship between Jewishness and queer identity in Tony Kushner's Angels in America; fictions concerning crypto-Jews in Cuba and the Mexican-American borderland; the connection between Jews and Christian apocalyptic narratives; stories of "new immigrants" by Bharathi Mukherjee, Gish Jen, Lan Samantha Chang, and Gary Shteyngart; and the revisionary relation of these authors to the classic Jewish American immigrant narratives of Henry Roth, Bernard Malamud, and Saul Bellow. By interrogating the fraught and multidimensional uses of Jews, Judaism, and Jewishness, Freedman deepens our understanding of ethnoracial complexities